Subverzivna mladinska književnost - pravljična igra Alenke Gerlovič Jurček in trije razbojniki (1944) v kontekstu - Blažič, Milena (Amfiteater (Ljubljana), 2021)
The article deals with the puppet play by the painter Alenka Gerlovič (1919–2010), entitled Jurček in trije razbojniki (Jurček (George/Georgie) and the Three Thieves). The play premiered at the Partisan Puppet Theater in 1944 and was published in 1950, with pictures from the puppet show. It is an expression of the author‘s ethical attitude towards Fascism and Nazism and the horrors of war. As the analysis shows, Alenka Gerlovič‘s play places her among the world‘s leading youth writers who have commented on the events of the war. Alenka Gerlovič uses Jurček to create an "imaginary screen" that allowed the audience to maintain a distance from the atrocities in the wartime situation and at the same time to be part of the anti-fascist struggle, also as a symbolic weapon and ethical act.
Keywords: 1944; Alenka Gerlovič; druga svetovna vojna; pravljična igra; puppet play; subversiveness; subverzivnost; World War II